2017
DOI: 10.7897/2230-8407.086100
|View full text |Cite
|
Sign up to set email alerts
|

Pharmagnostic Potentialities of Ceropegia Bulbosa Roxb. Var. Lushii (Grah.) HOOK.F.: An Endangered Plant From Thar Desert, Rajasthan, India

Abstract: Plants are important source of medicine and drugs, they contain many bioactive constituents that produce definite physiological and biochemical actions in the human body. Medicinal plants are great importance to the health of individuals and play a signifi cant role in traditional and modern drug system. Ceropegia bulbosa Roxb.var. lushii (Grah.) Hook.f. is one of the medicinally important and endangered plant (Asclepiadaceae), reported from some places of Rajasthan. The aim of present study was to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…Tetracontane is one of the major compounds which was only detected in flower samples at a retention time of 31.26 minutes with a peak area of 11.41%. Tetracontane is a natural product with anti-inflammatory, analgesic (Arora & Meena, 2017), antibacterial and antioxidant (Belkacemi et al, 2020;Indriati et al, 2021). Stigmast-5-en-3-ol, (3.beta.,24S)-(CAS) Clionasterol is known to have antiinflammatory, antipyretic, anti-ulcer, and antiarthritis (Arora & Meena, 2017).…”
Section: Analysis Of Bioactive Compounds On N-hexane Extractsmentioning
confidence: 99%
See 3 more Smart Citations
“…Tetracontane is one of the major compounds which was only detected in flower samples at a retention time of 31.26 minutes with a peak area of 11.41%. Tetracontane is a natural product with anti-inflammatory, analgesic (Arora & Meena, 2017), antibacterial and antioxidant (Belkacemi et al, 2020;Indriati et al, 2021). Stigmast-5-en-3-ol, (3.beta.,24S)-(CAS) Clionasterol is known to have antiinflammatory, antipyretic, anti-ulcer, and antiarthritis (Arora & Meena, 2017).…”
Section: Analysis Of Bioactive Compounds On N-hexane Extractsmentioning
confidence: 99%
“…Tetracontane is a natural product with anti-inflammatory, analgesic (Arora & Meena, 2017), antibacterial and antioxidant (Belkacemi et al, 2020;Indriati et al, 2021). Stigmast-5-en-3-ol, (3.beta.,24S)-(CAS) Clionasterol is known to have antiinflammatory, antipyretic, anti-ulcer, and antiarthritis (Arora & Meena, 2017). Ceropegia bulbosa extract contains tetracontane and stigmast-5-en-3-ol, (3.beta.,24S)-(CAS) clionasterol which has anti-inflammatory, analgesic, antipyretic, anti-ulcer, antiarthritis activity (Arora & Meena, 2017).…”
Section: Analysis Of Bioactive Compounds On N-hexane Extractsmentioning
confidence: 99%
See 2 more Smart Citations
“…211%). The compound of N-Hexadecanoic acid and Vitamin E has been noticed in plant extract exhibited in antioxidant and antibacterial activity [14,15]. Al-Salman et al [16] were reported that the compound of 2-Piperidinone, N-[4-Bromo-N-Butyl]-showed the strong antimicrobial activity.…”
Section: Gc-ms Analysismentioning
confidence: 99%